Nuts and seeds in health and disease prevention - Preedy, Victor R.; Watson, Ronald R. (Ronald Ross) (Academic Press, an imprint of Elsevier, 2020)
"Nuts and Seeds in Health and Disease Prevention, Second Edition investigates the benefits of nuts and seeds in health and disease prevention using an organizational style that will provide easy-access to information that supports identifying treatment options and the development of symptom-specific functional foods. This book examines seeds and nuts as agents that affect metabolism and other health-related conditions and explores the impact of compositional differences between various seeds and nuts, including differences based on country of origin and processing technique. Finally, the book includes methods for the analysis of seed and nut-related compounds"--Publisher's description